Esta é a Rádio Pan-Índia: nação, história e destino individual em Os filhos da meia-noite - Alexandre Isaac Siqueira (2014)
This study discuss the critics' readings of Salman Rushdie's Midnight's Children regarding the two biggest themes risen by this novel: history and nation. Saleem Sinai, the narrator, reflects openly about these two main themes, what led the critics to categorize the novel as post-colonial or post-modern. For the thinking of both categories, we analyze the concept of historical time that surrounds the novel. Because, besides the idea of diachronical series, we show how synchrony is essential not only for the idea of nation, but also for the narrator's claim of being handcuffed to history. We debate how an individual might claim being the image of a collectivity's history. We analyze Salman Rushdie's autobiography to look for more information about the subject. Because, due to the persecution of him and his books, he claims to be handcuffed to his time's history, like the narrator of his novel.